Typology of Characteristics of a Child’s Psyche in the Works of Mark Twain (As An Example of The Work "the Adventures of Tom Sawyer and Huckleberry Finn") - Ahmedjonovna, Azimova Dilnoza (European Journal of Life Safety and Stability (2660-9630), 2022)
American writer whose real name is Samuel Langhorne Clemens, a major representative of world literature. During his teenage years and youth, he spent his life as a laborer, engaged in various professions, earned his living, and later worked in newspaper editorial offices. His work covers many genres - realism, romanticism, humor, satire, philosophical fiction, journalism, etc., and in all these genres he invariably takes the position of a humanist and democrat.The literary heritage of Mark Twain entered the treasury of world culture, becoming the property of working humankind.The great democratic traditions in every national literature link the past with the present with a living thread sanctify with antiquity the noble struggle of advanced literature for the peace, freedom and happiness of humankind. Mark Twain’s portrayal of the two lovable characters in juxtaposition elucidating the dilemma of adolescence is subtly mirrored reflecting the constraints infused by the social order in our lives. This article deliberates upon the element of childhood and adolescence in two very popular works by the American author, Mark Twain.